Penyalahgunaan Kewenangan Direksi Dalam Peralihan Hak Atas Tanah Berdasarkan Perjanjian Pengikatan Jual Beli Dikaitkan Dengan Undang-Undang Perseroan Terbatas - Emilya Tunggal Manuain; Wira Franciska; Jelly Nasseri (JOURNAL of LEGAL RESEARCH, 2022)
The Board of Directors manages the firm in line with laws, rules, the articles of incorporation, and GMS decisions. Setbacks and lack of funds may force a company's board of directors to sell its assets. For legal processes to transfer or sell corporate assets, the company's articles of association must be examined, and if the transfer exceeds 50%, agreement from the Company's GMS is required. Taking the step by the board of directors will have legal consequences. This study uses normative legal research to get relevant data. The author used statutory methodology, authority, and legal consequences as analytical tools. Legal papers are studied by recognizing and cataloging grammatical and systematic interpretations of secondary data. The study obtained the authority of the board of directors, where in carrying out the responsibilities of managing the company is limited by laws and regulations, as stated in the articles of association of the PT in accordance with Article 100 paragraph (1) of the Limited Liability Company Law, and legal consequences for the parties in the case of misuse of such authority in the transfer. PPJB is agreement cancellation with compensation. In accordance with Civil Code Articles 1243 and 1244, which refer to the reimbursement of costs, damages, and interest in the case of a contract violation, parties aggrieved by the cancellation of the PPJB have filed a lawsuit for recovery of all costs and interest.